(untitled) (Netherlands, 2008)
This annually updated book provides a comprehensive overview of documentation relevant to M&A activities as well as selected country surveys. The book begins with country chapters that present the essential legislation for each country, providing an overview of the tax consequences of mergers, acquisitions, divisions and other transactions.
Keywords: Taxation,Hệ thống thuế